Analysis of the Collaborative Learning Application in Reading Material at Ninth Grade of SMPN 7 Kinali Pasaman Barat - Sukini Sukini; Hilma Pami Putri (Journal of English as A Foreign Language Teaching and Research, 2021)
This research was designed to find out and analyze of the collaborative learning application in reading material at ninth grade of SMPN 7 Kinali Pasaman Barat. This research conducted due to several problems found in the field which were students make a fuss when working in groups, students do not listen to given the assignment by the teacher. It can be seen that there were students who work on group assignments that care and others were just busy talking with others. This research was done in order to answer the research question “What were the role of student and what were the role of teacher in collaborative learning at the ninth grade of SMPN 7 Kinali Pasaman Barat?” This research was a qualitative research using collaborative learning strategy. The purpose of this research was to find out and analyze the collaborative learning applicationin reading material at the ninth grade of SMPN 7 KinaliPasaman Barat by analyzing the teacher’s and students’ role in the collaborative learning. The researcher used interview and observation as the instrument of the research. The interview was directed to both students and teacher, which for the students contained 12 questions and for the teacher contained 7 questions. The researcher took 2 classes namely IX1 and IX2 as the observation object.                    Based on the finding from interview and observation of the collaborative learning in SMPN 7 Kinali Pasaman Barat, it was found that the teacher already fulfilled her role in the collaborative learning effectively, in the other hand the students still lack of the role as the cheer leader. They still laughed at their friends mistake. Besides that, the other roles that the students supposed to have were already done effectively. As the conclusion, the collaborative learning in SMPN 7 Kinali Pasaman Barat was good since the students and the teacher were doing their role effectively